Suicidal ideation and long work hours by gender in Korean employees: The Kangbuk Samsung Workplace Mental Health Study: A cross-sectional study - Heejun Lee; Sung Joon Cho; Young-Chul Shin; Dong-Won Shin; Jae-Hyun Park; Mukyeong Kim; Kang-Seob Oh; Sang-Won Jeon (Precision and Future Medicine, 2022)
Purpose This study investigated the relationship between increased working hours and suicidal ideation among Korean full-time employees by gender. Methods Participants were employees from 54 companies and local government organizations in Korea, aged 19 to 68, who completed a self-reported questionnaire on sociodemographic factors, daily perceived stress, resilience, depressive symptoms, and suicidal ideation. Of the initial 15,360 respondents, participants who worked less than 40 hours were excluded. The final sample size was 9,326 (5,652 men, 3,674 women). Sociodemographic factors and psychological characteristics of participants with suicidal ideation were analyzed using Student’s t-tests and chi-square tests for continuous and categorical variables, respectively. Hierarchical logistic regression analyses were performed using suicidality as the dependent variable respectively for all participants, for male, and female. Furthermore, we used these results to compare differences between men and women associated with regard to long working hours to better understand how long working hours correlate with suicidal ideation; further, we examined the impact of gender on this relationship. Results In univariate analyses, suicidal ideation was associated with increased working hours. Hierarchical logistic regression analyses of sociodemographic and psychological factors found no association between long working hours and suicidal ideation for the participants overall. However, they showed significant differences between men and women, such that long working hours were associated with suicidal ideation in men but were non-significant for women. Conclusion Suicidal ideation is associated with long working hours among Korean male full-time workers, while other factors are more likely to lead to suicidal ideation among female workers. Suicide prevention measures for employees should thus be developed based on gender.